"Canonical and non-canonical actions of GRK5 in the heart". (March 2016) - Traynham, Christopher J.; Hullmann, Jonathan; Koch, Walter J.
Abstract: As the average world-wide lifespan continues to increase, heart failure (HF) has dramatically increased in incidence leading to the highest degree of mortality and morbidity of any disease presently studied. G protein-coupled receptors (GPCRs) play a prominent role in regulation of cardiovascular function. GPCRs are effectively "turned off" by GPCR kinases (GRKs) in a process known as "desensitization". GRKs 2 and 5 are highly expressed in the heart, and known to be upregulated in HF. Over the last 20 years, the role of GRK2 in HF has been widely studied. However, until recently, the role of GRK5 in cardiac pathophysiology had yet to be elucidated. In the present review, we will focus on GRK5's role in the myocardium in normal physiology, and its apparent critical role in the progression of HF. Further, we will also present potential therapeutic strategies (i.e. small molecule inhibition, gene therapy) that may have potential in combating the deleterious effects of GRK5 in HF. Highlights: GRK5 acts as a hypertrophic facilitator only under pathological conditions. The beneficial effects of physiological hypertrophy are due to a non-GRK5 event. Inhibition of GRK5 nuclear targeting may be a novel therapeutic strategy in disease.